Unmasking Hb Paksé (codon 142, TAA>TAT, α2) and its combinations in patients also carrying Hb constant spring (codon 142, TAA>CAA, α2) in Northern Thailand - Pornprasert S. (2017)
The incidence of Hb Paksé (codon 142, TAA > TAT, α2) might have been underestimated due to misidentifying some cases as Hb Constant Spring (Hb CS, codon 142, TAA > CAA, α2) since both abnormal hemoglobins (Hbs) migrate to the same position on Hb electrophoresis or chromatography. Multiplex asymmetric allele-specific polymerase chain reaction (PCR) for identification of Hb CS and Hb Paksé, and a real-time PCR (ReTi-PCR) with SYBR Green1 high resolution melting (HRM) analysis, for detection of the α-thalassemia-1 (α-thal-1) Southeast Asian ( SEA /) type deletion, were performed on 114 blood samples collected from subjects who lived in northern Thailand. These samples were previously identified as carrying Hb CS by capillary electrophoresis (CE) or high performance liquid chromatography (HPLC). Five out of 114 (4.4) samples were found to carry Hb Paksé with four different genotypes including Hb Paksé trait, compound Hb CS/Hb Paksé, Hb H-Hb Paksé disease and Hb H-Hb Paksé-Hb E disease. These results suggested that Hb Paksé and its various combinations can be misidentified as Hb CS. Although the clinical symptoms of Hb Paksé and Hb CS are similar, to prevent erroneous epidemiological data on Hb CS as well as underestimating the prevalence of Hb Paksé in northern Thailand, DNA analysis is recommended to be performed in all cases when peaks of Hb CS/Hb Paksé are detected on CE or HPLC. © 2012 Informa Healthcare USA, Inc.